Desensitization of 5-HT1A Receptors by 5-HT2A Receptors in Neuroendocrine Neurons in Vivo - Zhang, Yahong; Gray, Thackery S.; D’Souza, Deborah N.; Carrasco, Gonzalo A.; Damjanoska, Katerina J.; Dudas, Bertalan; Garcia, Francisca; Zainelli, Gina M.; Sullivan Hanley, Nicole R.; Battaglia, George; Muma, Nancy A.; Van de Kar, Louis D. (The Journal of pharmacology and experimental therapeutics, 2004)
An imbalance between serotonin-2A (5-HT2A) and 5-HT1A receptors may underlie several mood disorders. The present studies determined whether 5-HT2A receptors interact with 5-HT1A receptors in the rat hypothalamic paraventricular nucleus (PVN). The sensitivity of the hypothalamic 5-HT1A receptors was measured as oxytocin and adrenocorticotropic hormone (ACTH) responses to the 5-HT1A receptor agonist (+)-8-hydroxy-2-(di-n-propylamino) tetralin hydrobromide [(+)8-OH-DPAT] (40 μg/kg s.c.). The 5-HT2A/2C receptor agonist (-)DOI [(-)-1-(2,5-dimethoxy-4-iodophenyl)2-aminopropane HCl] (1 mg/kg s.c.) injected 2 h prior to (+)8-OH-DPAT significantly reduced the oxytocin and ACTH responses to (+)8-OH-DPAT, producing a heterologous desensitization of the 5-HT1A receptors. Microinjection of the 5-HT2A receptor antagonist MDL100,907 [(+)-α-(2,3-dimethoxyphenyl)-1-[2-(4-fluorophenylethyl)]-4-piperidinemethanol; 0, 10, or 20 nmol, 15 min prior to (-)DOI] into the PVN dose-dependently prevented the desensitization of 5-HT1A receptors induced by the 5-HT2A receptor agonist (-)DOI. Double-label immunocytochemistry revealed a high degree of colocalization of 5-HT1A and 5-HT2A receptors in the oxytocin and corticotropin-releasing factor neurons of the PVN. Thus, activation of 5-HT2A receptors in the PVN may directly induce a heterologous desensitization of 5-HT1A receptors within individual neuroendocrine cells. These findings may provide insight into the long-term adaptation of 5-HT1A receptor signaling after changes in function of 5-HT2A receptors; for example, during pharmacotherapy of mood disorders.